Neotectonics and tectonic stresses of the Sakhalin Island - L. A. Sim; L. M. Bogomolov; G. V. Bryantseva; P. A. Savvichev (Геодинамика и тектонофизика, 2017)
The paper describes the neotectonics of the Sakhalin Island and analyzes the latest and recent tectonic stresses in the study area in order to establish their differences in the Amur and Okhotsk microplates, which boundary is confined to the Tym-Poronaisk fault, the largest NS-striking fault in the Central Sakhalin (Fig. 1). Our map of the structural geomorphological features of the study area (Fig. 2) shows three longitudinal zones: the western and eastern uplifts, and the Central Sakhalin basin between the uplifts. In the Southern Sakhalin, neotectonic stresses were studied by a combination of tectonophysical methods and the method of structural geology (Figures 3 to 6, and Table). Our study shows that the regional axes of maximum and minimum compressive principal normal stresses are primarily of the subhorizontal orientations (Fig. 5, Д). In the Northern and Central Sakhalin, neotectonic stresses were reconstructed by the structural geomorphology method. The compression axes are oriented sublatitudinally, with the NE-trending strike in the Northern Sakhalin (Fig. 7, A), and the extension axes are oriented submeridionally; in the Northern Sakhalin, respectively, they are oriented in the NW direction. The results of our study of neotectonic stresses were used to construct a map of recent geodynamics of Sakhalin (Fig. 7, Б), which shows zones differing in the geodynamic settings of the most recent faulting. According to the analysis of the recent tectonic stress with respect to the earthquake focal mechanisms in the period from 1978 to 2015 (Fig. 8), recent stresses dominating in Sakhalin have mainly the sublatitudinal low-angle orientations of the deviatoric compression axis. The submeridional low-angle orientations of the deviatoric extension axes are observed in the Northern Sakhalin and partly in the north of the Southern Sakhalin (see Fig. 8). The high-angle axes of deviatoric extension are typical of the western and central parts of the Southern Sakhalin, and such extension leads to horizontal compression and reverse faulting. In some areas of the recent stress field, the deviatoric axes of compression and extension have unstable orientations. The latitudinal boundaries of such areas are nearly coincident with the boundaries of the zones that differ in the geodynamic settings of the most recent faulting, which means that these areas and zones are reliably identified. The relative inhomogeneity of the neotectonic and recent stress fields in the Southern Sakhalin does not give grounds to distinguish differences in the state of crustal stresses in the areas located on the sides of the Southern Sakhalin fault. As a consequence, a boundary between the Amur and the Okhotsk Plate in the South Sakhalin cannot be drawn along this fault. It is most likely that this boundary coincides with the Western-Sakhalin fault in the southern areas of the study region. Our data on the Central and Northern Sakhalin does not contradict with the conclusion in [Savostin et al., 1982] concerning this boundary.